Allyl Isothiocyanate: A TAS2R38 Receptor-Dependent Immune Modulator at the Interface Between Personalized Medicine and Nutrition - Tran, Hoai T. T.; Stetter, Rebecca; Herz, Corinna; Spöttel, Jenny; Krell, Mareike; Hanschen, Franziska S.; Schreiner, Monika; Rohn, Sascha; Behrens, Maik; Lamy, Evelyn (Frontiers in Immunology, 2021)
Understanding individual responses to nutrition and medicine is of growing interest and importance. There is evidence that differences in bitter taste receptor (TAS2R) genes which give rise to two frequent haplotypes, TAS2R38-PAV (functional) and TAS2R38-AVI (non-functional), may impact inter-individual differences in health status. We here analyzed the relevance of the TAS2R38 receptor in the regulation of the human immune response using the TAS2R38 agonist allyl isothiocyanate (AITC) from Brassica plants. A differential response in calcium mobilization upon AITC treatment in leucocytes from healthy humans confirmed a relevance of TAS2R38 functionality, independent from cation channel TRPV1 or TRPA1 activation. We further identified a TAS2R38-dependence of MAPK and AKT signaling activity, bactericidal (toxicity against E. coli) and anti-inflammatory activity (TNF-alpha inhibition upon cell stimulation). These in vitro results were derived at relevant human plasma levels in the low micro molar range as shown here in a human intervention trial with AITC-containing food.